The power of controversy - the role of competitiveness - Kuemmel, Leif Louis (2022)
It is becoming increasingly relevant for companies to take a stand on socio-political issues, because more and more consumers are basing their purchasing behavior on the principles of brands. The aim of this study is to determine what role personality-based competitiveness plays in the perception and purchase intention of controversial brands. To answer this question, two quantitative studies have been administered through online surveys. The analysis of the quantitative study could not provide any evidence that points to this hypothesized connection. However, indications of previously unknown correlations in terms of gender were discovered, which could be interesting for future research.